PEMANFAATAN LIDAH BUAYA (Aloe vera) SEBAGAI ANTI MIKROBA DAN ANTI DIABETES MELLITUS - Marina Silalahi (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
Aloe vera (Aloe vera) is a multifunctional plant which easily found in various yards. Processed AV leaves are used as food, medicine and cosmetics, but in-depth and comprehensive studies of their bioactivity are still limited. The writing of this article is based on the study of literature in various books, the results of research published on line and off line. Aloe vera has long been used as a wound drug and a drug for diabetes mellitus. The use of Aloe vera as a wound medicine is related to its ability to inhibit the growth of microbes (bacteria and fungi). Research shows that AV extracts inhibit the growth of Streptococcus mutans, Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Bacteroides fragilis, Mycobacterium smegmatis, Staphylococcu aureus, Enterococcus faecalis, Micrococcus luteus Bacillus sphericaus, Cholesterolus, Cholesterolus, Cholesterolus. The use of Aloe vera as a diabetes mellitus drug is related to its ability to improve the function of the pancreas in producing insulin..